The didactic potential of cloud technologies in the study of computing disciplines by bachelors in system analysis - O. F. Diachenko (Academy of Cognitive and Natural Sciences, 2017)
Research goals: improvement of a technique of development of information and communication competence of students of specialty "System analysis" using cloud technologies in the process of studying technical disciplines. Research objectives: to reveal the didactic potential of cloud computing for the development of ICT competence of students while studying computing. Object of research: process of training of bachelors in system analysis. Subject of research: methods of development of ICT competence of bachelors in system analysis with the use of cloud technologies in teaching computing. The results of the study: refined didactic potential of cloud computing in teaching computing, which contributes to professional and practice-oriented focus of educational outcomes and development of ICT competence of bachelors in system analysis.